2008
DOI: 10.1073/pnas.0800620105
|View full text |Cite
|
Sign up to set email alerts
|

Promoter ChIP-chip analysis in mouse testis reveals Y chromosome occupancy by HSF2

Abstract: The mammalian Y chromosome is essential for spermatogenesis, which is characterized by sperm cell differentiation and chromatin condensation for acquisition of correct shape of the sperm. Deletions of the male-specific region of the mouse Y chromosome long arm (MSYq), harboring multiple copies of a few genes, lead to sperm head defects and impaired fertility. Using chromatin immunoprecipitation on promoter microarray (ChIP-chip) on mouse testis, we found a striking in vivo MSYq occupancy by heat shock factor 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
91
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 38 publications
(57 reference statements)
11
91
0
1
Order By: Relevance
“…Whereas HSF1, which is the major stressactivated regulator, binds to continuous HSEs, both HSF2 and HSF4 bind preferentially to discontinuous HSEs. Our findings are also consistent with previous evidence that different HSFs can have targets in common (Akerfelt et al, 2008;Fujimoto et al, 2008;Yamamoto et al, 2009). Whereas the DNA-binding domains of the three HSFs identified in mammalian cells are highly similar (70.5% identity between HSF1 and HSF2, 76.2% identity between HSF1 and HSF4 and 62.4% identity between HSF2 and HSF4), HSFs nevertheless show different DNA-binding preferences (Somasundaram and Bhat, 2004;Fujimoto et al, 2004Fujimoto et al, , 2008Yamamoto et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Whereas HSF1, which is the major stressactivated regulator, binds to continuous HSEs, both HSF2 and HSF4 bind preferentially to discontinuous HSEs. Our findings are also consistent with previous evidence that different HSFs can have targets in common (Akerfelt et al, 2008;Fujimoto et al, 2008;Yamamoto et al, 2009). Whereas the DNA-binding domains of the three HSFs identified in mammalian cells are highly similar (70.5% identity between HSF1 and HSF2, 76.2% identity between HSF1 and HSF4 and 62.4% identity between HSF2 and HSF4), HSFs nevertheless show different DNA-binding preferences (Somasundaram and Bhat, 2004;Fujimoto et al, 2004Fujimoto et al, , 2008Yamamoto et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Given the cell-type specificity of HSF actions (Fujimoto and Nakai, 2010) it seems likely that the effects of HSFs on HIF-1a transcription observed in human breast cancer cells may differ in other cell types and may also be affected differently by heat shock and other stress conditions in different cell types (see Mathew et al, 2001;Pirkkala et al, 2001;Chi and Karliner, 2004;Xing et al, 2005;Loison et al, 2006;Akerfelt et al, 2007Akerfelt et al, , 2008Ostling et al, 2007;Sandqvist et al, 2009;Yamamoto et al, 2009). However, notwithstanding these considerations, our data show that the effects of HSF2 and HSF4 on VEGF production in at least two other cell lines-HeLa and 293T cells-are similar to those seen in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the molecular targets of HSF2 during spermatogenesis were identified at the genome-wide level by Akerfelt et al (2008). High-resolution chromatin immunoprecipitation (ChIP)-on-chip analysis using promoter microarrays to assay HSF2-binding sites in adult mouse testes revealed that HSF2 primarily interacts with sites on the mouse Y chromosome.…”
Section: Dna-binding Proteins That Regulate Spermatogenesismentioning
confidence: 99%
“…This study by Akerfelt et al (2008) is a landmark paper, as it is one of very few studies to perform genome-wide analysis of transcription factor-binding sites in vivo rather than in cultured cells. It remains for future studies to determine precisely how HSF2 controls male fertility and whether it directly or indirectly controls chromatin structure.…”
Section: Dna-binding Proteins That Regulate Spermatogenesismentioning
confidence: 99%